Muco-cutaneous presentation of Behcet's disease. Concordance of therapeutic approaches. Case report and literature review - Paucar-Lescano, Patricia K. (2022)
Behçet's disease (BD) is a chronic systemic inflammatory vasculitis of recurrent-remitting course, of unclear etiology, described in patients who had as a triggering factor: bacterial infections, viral infections, and abnormal autoantigens in patients with a genetic predisposition. It can be recognized by clinical findings due to the absence of a universally accepted diagnostic laboratory test. Oral and genital ulcers, as well as cutaneous vasculitis lesions are considered markers of BD and frequently precede other manifestations. Mucocutaneous lesions figure prominently in the presentation and diagnosis, therefore their recognition can allow its early diagnosis and treatment, with beneficial results for the patient's prognosis, but they are not the only lesions that this disease presents, which is why it was performed a literature review.